Efisiensi Teknis dan Faktor Produksi yang Mempengaruhi Usahatani Padi Sawah Tadah Hujan (Studi Kasus Di Desa Bonto Mate'ne Kecamatan Marusu Kabupaten Maros) - Mardiana Amir; Arifin Arifin; Abd. Asis Pata (Universitas Muslim Maros, 2022)
This study aims to determine the level of technical efficiency and production factors that affect rainfed lowland rice farming in Bonto Mate'ne Village, Marusu District, Maros Regency. The data used in this study are primary data and secondary data with analytical methods using quantitative data analysis. The sample in this study was taken by 25 respondent farmers. The results showed that rainfed lowland rice farming in Bonto Mate'ne Village, Marusu District, Maros Regency was not technically efficient, obtained an average technical efficiency of 0.77 or reached 77% of the potential production obtained from the combination of production used. and there is still a 23% chance to increase rice production. And the production factors that affect rainfed lowland rice farming are land area and the amount of fertilizer while pesticides have no significant effect on rainfed lowland rice farming production.